2017
DOI: 10.1007/s11240-017-1287-3
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic cowpeas (Vigna unguiculata L. Walp) expressing Bacillus thuringiensis Vip3Ba protein are protected against the Maruca pod borer (Maruca vitrata)

Abstract: A vip3Ba gene reconstructed for plant expression was used in transforming cowpea via Agrobacterium tumefaciens. Transgenic lines expressing Vip3Ba protein were used in insect feeding trials to assess protection against Maruca and were found to be completely protected from this pest. We propose that the vip-cowpea lines could be combined with existing cry-transgenic cowpea to introgress this additional resistance trait and thus avoid or greatly delay the development of resistance in Maruca.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 73 publications
2
25
0
Order By: Relevance
“…Cow pea is an important food crop in many African countries, and is harmed by Lepidopteron pest, Maruca vitrata (Family: Crambidae). The Vip3Ba1 gene, isolated from Australian Bt isolates, was transformed and expressed in cowpea to provide protection against legume pod borer (M. vitrata), by strongly inhibiting larvae growth [93]. Similarly, a transgenic corn event (C008 and C010) expressing Vip3Aa19 has been found to be highly toxic against black cut worm [94].…”
Section: Transgenic Crops Expressing Vip Proteinsmentioning
confidence: 99%
“…Cow pea is an important food crop in many African countries, and is harmed by Lepidopteron pest, Maruca vitrata (Family: Crambidae). The Vip3Ba1 gene, isolated from Australian Bt isolates, was transformed and expressed in cowpea to provide protection against legume pod borer (M. vitrata), by strongly inhibiting larvae growth [93]. Similarly, a transgenic corn event (C008 and C010) expressing Vip3Aa19 has been found to be highly toxic against black cut worm [94].…”
Section: Transgenic Crops Expressing Vip Proteinsmentioning
confidence: 99%
“…This contradicted Omo-Ikerodah et al (2009) findings where reciprocal differences were important in conditioning resistance to flower thrips among cowpea genotypes. However, the occurrence of significant reciprocal by location interaction effects (Table 5) between the reciprocal families indicated that the expression of the cytoplasmic factors on thrips damage scores depended on the environmental factors as well as in the case of the nuclear genes (Boukar et al, 2013;Bett et al, 2017;Oladejo et al, 2017). Consequently, the use of the resistant genotype as female parent could confer superior resistance on the F2s in different locations.…”
Section: Discussionmentioning
confidence: 99%
“…The transgenic Bt cowpea lines, when evaluated in the field, showed high levels of resistance to Maruca as the larvae which are responsible for causing damages on cowpea flowers, pods, seeds, and young shoots were killed following their feeding on the plant (Mohammed et al, 2014). One major limitation of the Bt genes is their poor expression in higher eukaryotes (Bett et al, 2017), and a second limitation is their selective properties that target mostly Lepidopteran species. This implies that cowpea farmers who adopt these transgenic varieties will still need to protect their crops against other insect pests that are not controlled by Bt gene.…”
Section: Introductionmentioning
confidence: 99%